Effect of light and temperature on Cercospora coffeicola and Coffe arabica pathosystem - Silva, Marilia Goulart; Pozza, Edson Ampélio; Monteiro, Fernando Pereira; Lima, Caio Vitor Rodrigues Vaz (Coffee Science - ISSN 1984-3909, 2016)
The mycelial growth rate (MGR), in vitro production of cercosporin, and intensity (incidence and severity) of Cercospora leaf spot on coffee seedlings ‘Catuaí Vermelho IAC 144’ were evaluated under different light intensities (80, 160,240, and 320 μmol m-2 s-1) and temperatures (17, 21, 25, and 29°C). Dark condition (0 μmol m-2 s-1) was also included in in vitro experiments. In vivo, were evaluated incidence, severity, rates of chlorophyll a, b, and total in healthy (without symptoms) and sick tissues (with symptoms), and the photosynthetic rate and variables affecting it, were also evaluated. All the experiments were done at least two times. In in vitro experiments, the highest mycelial growth rate (MGR) was observed at 24.1°C in the dark condition (0 μmol m-2 s-1), while the highest amount of toxin occurred at 24.9°C and light intensity 320 μmol m-2 s-1. When dishes were incubated in the dark, the lowest levels of cercosporin were produced by the pathogen, regardless of temperature,thus confirming the importance of light in the activation of toxin production. In in vivo experiments, the highest incidence and severity progress of the disease were observed at 21°C. With respect to the amounts of chlorophyll a, b, and total, regardless of treatment, the lowest levels were found in the area of the leaf with symptons compared to the area without symptoms. Photosynthesis correlated positively with temperature and negatively with internal carbon. These results elucidate the effect of the interaction between temperature and light intensity, contributing to future studies with this pathosystem.